Full-Endoscopic Lumbar Decompression with Minimal Nerve Root Retraction for Impending Neurologic Deficit in Degenerative Lumbar Spine Diseases - Kim, Hyeun Sung; Raorane, Harshavardhan Dilip; Choi, Il; Wu, Pang Hung; Yang, Kyung Hoon; Yi, Yeon Jin; Jang, Il Tae (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Objectives The aim of this retrospective case study was to analyze the outcomes of minimal nerve root retraction in patients with impending neurologic deficit in degenerative lumbar spine disease using the full-endoscopic spine surgery.Materials and Methods Thirty-seven consecutive patients with impending neurologic deficit underwent endoscopic spine surgery through either the transforaminal or the interlaminar approach. Their clinical outcomes were evaluated with visual analog scale (VAS) leg pain score, Oswestry Disability Index (ODI), and MacNab's criteria. The outcome of motor deficitis was evaluated with the Medical Research Council (MRC) grade. Completeness of decompression was documented with a postoperative magnetic resonance imaging (MRI) and computed tomography (CT) scan.Results A total of 40 lumbar levels of 37 patients were operated, VAS score of the leg improved from 7.7 ± 1 to 1.9 ± 0.6 (p < 0.0001). ODI score improved from 74.7 ± 6.5 to 25.4 ± 3.49 (p < 0.0001). Motor weakness improved significantly immediately after surgery. The mean MRC grade increased to 1.97, 3.65, 4.41, and 4.76 preoperatively, at 1 week, at 3 months, and at the final follow-up, respectively, and all the patients with foot drop and cauda equina syndrome symptom recovered completely. One patient with great toe drop recovered partially to MRC grade 3. Mean follow-up of the study was 13.3 ± 6.1 months. According to MacNab's criteria, 30 patients (80.1%) had good and 7 patients (18.9%) had excellent results. Three patients required revision surgery.Conclusions Minimal nerve root retraction during full-endoscopic spine surgery is safe and effective for treatment of the impending neurologic deficit. We could achieve a thorough decompression of the affected nerve root with acceptable clinical outcome and minimal postoperative morbidity.
Keywords: minimal nerve root retraction; impending neurologic deficit; transforaminal endoscopic lumbar diskectomy; interlaminar endoscopic lumbar diskectomy; endoscopic spine surgery